The Dialectics of Mobility: Capitalism and Apocalypse in Cormac McCarthy’s The Road - Simon Schleusener (European Journal of American Studies)
In the post-apocalyptic setting of Cormac McCarthy’s novel The Road (2006), a father and his son “push down the road a battered shopping cart, containing their bare provisions, on a thoroughly consumed earth” (Seltzer 189). Despite the fact that the novel seems to be situated in an indistinct no-man’s-land, marked by a curious absence of time and history, this essay argues that it is indeed worthwhile to historicize The Road. By placing the novel in the context of the new capitalism, the article explores the ways in which McCarthy’s treatment of mobility deviates from previous American road narratives, which typically celebrate the pleasures and possibilities of movement and flight. Concentrating on the novel’s dystopian “catastrophism,” the essay will further investigate its relation to temporality, history, and the future.